A systematic literature review on less common natural fibres and their biocomposites. (10th September 2018) - Sarasini, F.; Fiore, V.
Abstract: Interest in utilization of renewable resources is increasing because of public's environmental awareness and economic considerations. Lignocellulosic fibres have already attracted growing attention as reinforcement of polymeric matrices instead of synthetic ones (mainly glass) from the academic and industrial fields. In addition to kenaf, hemp, sisal, flax and jute, which are the subject of extensive investigations for composite applications since the 1970s, in the last years several researchers suggested the use of less common natural fibres, due to their low cost and availability. This paper reviews the extraction methods, chemical, morphological, thermal and mechanical properties of these less exploited natural fibres reported in literature, discussing their advantages and challenges through comparison against various traditional plant fibres. The introduction of these less common natural fibres in thermoplastic and thermosetting matrices is critically discussed and compared with several standard biocomposites. These renewable and less investigated plant fibres can also be regarded as a source of nanocellulose aimed to enhance the green character of the final composites, thus pushing the industry to move towards such environmentally friendly materials. Highlights: A comprehensive review of less common natural fibres is done. Literature studies on new green materials made of less common natural fibres and polymer matrices are reviewed. The introduction of less common natural fibres in polymeric matrices is compared with the traditional natural fibres. The development of cellulose-based nanocomposites is presented and discussed.